Skin resurfacing procedures: new and emerging options - Loesch MM; Somani AK; Kingsley MM; Travers JB; Spandau DF (Dove Medical Press, 2014)
Mathew M Loesch,1 Ally-Khan Somani,1 Melanie M Kingsley,1 Jeffrey B Travers,1–3 Dan F Spandau1,41Department of Dermatology, 2Department of Pharmacology and Toxicology, 3Department of Pediatrics, 4Department of Biochemistry and Molecular Biology, Indiana University School of Medicine, Indianapolis, IN, USAAbstract: The demand for skin resurfacing and rejuvenating procedures has progressively increased in the last decade and has sparked several advances within the skin resurfacing field that promote faster healing while minimizing downtime and side effects for patients. Several technological and procedural skin resurfacing developments are being integrated into clinical practices today allowing clinicians to treat a broader range of patients' skin types and pathologies than in years past, with noteworthy outcomes. This article will discuss some emerging and developing resurfacing therapies and treatments that are present today and soon to be available.Keywords: rejuvenation, wounding, non-melanoma skin cancer, therapy